Observations on the composition of Aristophanes’ scholia (Minerva, 2025)
This paper studies the composition of Aristophanes’ scholia, focusing on the notes that refer to five types of text belonging to the philological tradition of Antiquity: editions, commentaries (hypomnémata), catalogues, monographs, and lexicography. The study shows the extent to which Aristophanes’ scholia draw on the Hellenistic and Imperial philology but also reveals the main areas of interest of the medieval scholiasts on Aristophanes.
Keywords: scholia; Aristophanes; philology; exegesis; hypomnémata